Erratum: Pengaruh Bahan Ajar Pendidikan Jasmani Terintegrasi dengan ISMUBA Bagi Siswa SD Muhammadiyah - Agung Widodo; Muhammad Thariq Aziz (STKIP Muhammadiyah Kuningan, 2020)
Correction to: JUARA: Jurnal Olahraga This corrects the article DOI: https://doi.org/10.33222/juara.v4i2.499 This article was originally published using English metadata in the article title and this is our fault. but now the article metadata has been changed in Indonesian and appears correctly in the current article.